Categorization and Extraction of chitin; a functional biopolymer derived from scales of common carp fish (Cyprinus carpio l.): A stress free source - Davison, George; Sebastian, Victor; Lebechi (Advances in Aquaculture and Fisheries Management, 2013)
Chitin is the most abundant natural amino polysaccharide and is estimated to be produced annually almost as much as cellulose. It has become of great interest not only as an industrialized resource, but also as a new functional material of high potential in various fields. Chitin was successfully extracted from the scales of a common Carp fish and characterized for it functional properties. Structural data of the chitin was determined by FT-IR and the crystalline and surface morphology were also studied by Powder X-Ray diffractometry and scanning electron microscopy (SEM). The proximate analysis determined was 2.12% moisture content, 1.56% ash and 4.18% Nitrogen. The amount of Ca, Mg, Zn, Fe, Cu and Mn present in the chitin was 26.84, 50.49, 21.80, 12.68, 0.22 and 1.17 mg/kg, obtained by atomic absorption spectrometry, respectively.